2015
DOI: 10.5772/61661
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of α-Silicon Nitride Nanowires from Silicon Monoxide on Alumina

Abstract: Silicon nitride nanowires were synthesized using silicon monoxide as raw materials and an alumina plate as substrate at 1500°C. The obtained nanowires were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, high-resolution transmission electron microscopy and thermogravimetricdifferential scanning calorimetry. The results revealed that silicon nitride nanowires possess a diameter of about 200 nm and a length of several hundred micrometres. The preferred g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Ordered arrays of α-Si 3 N 4 nanowires have been also synthesized at 1150 • C with NH 3 [45,46]. Direct synthesis of α-Si 3 N 4 nanowires from silicon monoxide on alumina with N 2 /H 2 was also reported [47]. Similarly, it has been demonstrated that single-crystalline α-Si 3 N 4 nanowires can grow in a direction perpendicular to the wet-etched trenches in the SiO film on the plane of the Si substrate without metal catalysis [33].…”
Section: Discussionmentioning
confidence: 99%
“…Ordered arrays of α-Si 3 N 4 nanowires have been also synthesized at 1150 • C with NH 3 [45,46]. Direct synthesis of α-Si 3 N 4 nanowires from silicon monoxide on alumina with N 2 /H 2 was also reported [47]. Similarly, it has been demonstrated that single-crystalline α-Si 3 N 4 nanowires can grow in a direction perpendicular to the wet-etched trenches in the SiO film on the plane of the Si substrate without metal catalysis [33].…”
Section: Discussionmentioning
confidence: 99%
“… The Si gas was then transported by the swirling updraft flow to the graphite substrate above the crucible to react with N 2 according to eq , resulting in the nucleation and growth of Si 3 N 4 nanofibers. Such reaction is thermodynamically preferred according to the results in (Figure S6) and is found in other works Because there is some SiO gas in the system and the nucleation of the nanofiber is on a graphite substrate, eq may partially contribute to the nucleation of Si 3 N 4 nanofiber. As a result, the above-mentioned five equations are responsible for the formation and transportation of the Si source and nucleation and growth of the Si 3 N 4 nanofiber sponge.…”
Section: Fabrication Methods and Microstructure Of The Si3n4 Nanofibe...mentioning
confidence: 99%
“…In its various one-dimensional (1D) forms, such as nanowires (NWs) and nanobelts (NBs), silicon nitride (Si 3 N 4 ) , not only possesses the outstanding properties of its bulk counterpart but also displays its own unique properties. These include superior photoelectric and mechanical properties, making Si 3 N 4 nanostructures potentially useful in many important areas, such as nanoelectronics, energy conversion and storage, lasers, chemical sensing and catalysis, and light/field emission devices, nanodevices, nanocomposites, , and reinforcement materials . A range of methods to synthesize Si 3 N 4 1D nanostructures with various morphologies (e.g., nanobelts, nanodendrites, and nanosheets) have been attempted and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 As Si 3 N 4 could prove an excellent host material, in terms of its mechanical strength, thermal/chemical stability, and high dopant concentration, 25,26 it is considered a promising candidate for high-temperature microelectronic and optoelectronic applications, 27,28 and for use in high-radiation environments. 24 In its various one-dimensional (1D) forms, such as nanowires (NWs) and nanobelts (NBs), silicon nitride (Si 3 N 4 ) 29,30 not only possesses the outstanding properties of its bulk counterpart but also displays its own unique properties. 31−33 These include superior photoelectric and mechanical properties, making Si 3 N 4 nanostructures potentially useful in many important areas, such as nanoelectronics, energy conversion and storage, lasers, chemical sensing and catalysis, and light/ field emission devices, 25 nanodevices, nanocomposites, 34,35 and reinforcement materials.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation